Effect of nonsurgical periodontal therapy verses oral hygiene instructions on type 2 diabetes subjects with chronic periodontitis: a randomised clinical trial - Raman, R.P.C.; Taiyeb-Ali, T.B.; Chan, S.P.; Chinna, K.; Vaithilingam, R.D. (BioMed Central, 2014)
BACKGROUND: 40 subjects with type 2 diabetes and moderate to severe CP were randomly distributed to groups receiving either NSPT or OHI. Periodontal parameters, glycosylated haemoglobin (HbA1c) and high-sensitivity C-reactive protein (hs-CRP) were evaluated at baseline, 2- and 3-months intervals. METHODS: 40 subjects with type 2 diabetes and moderate to severe CP were randomly distributed to groups receiving either NSPT or OHI. Periodontal parameters, glycosylated haemoglobin (HbA1c) and high-sensitivity C-reactive protein (hs-CRP) were evaluated at baseline, 2- and 3-months intervals. RESULTS: 15 subjects from NSPT group and 17 from OHI group completed the study. The difference in plaque index (PI) between NSPT and OHI groups were significant at 2 months recall (p = 0.013). There was no significant difference between NSPT and OHI group for all other clinical periodontal parameters, HbA1c and CRP levels. At 3 months post-therapy, periodontal parameters improved significantly in both groups with sites with probing pocket depth (PPD) < 4 mm reported as 98 ± 1.8% in NSPT group and 92 ± 14.9% in OHI group. Mean PPD and mean probing attachment loss (PAL) within the NSPT group reduced significantly from baseline (2.56 ± 0.57 mm, 3.35 ± 0.83 mm) to final visit (1.94 ± 0.26 mm, 2.92 ± 0.72 mm) (p = 0.003, p < 0.001). For OHI group, improvements in mean PPD and mean PAL were also seen from baseline (2.29 ± 0.69 mm, 2.79 ± 0.96 mm) to final visit (2.09 ± 0.72 mm, 2.62 ± 0.97 mm) (p < 0.001 for both). Similarly, HbA1c levels decreased in both groups with NSPT group recording statistically significant reduction (p = 0.038). Participants who demonstrated ≥ 50% reduction in PPD showed significant reductions of HbA1c and hs-CRP levels (p = 0.004 and p = 0.012). CONCLUSION: NSPT significantly reduced PI at 2 months post-therapy as compared to OHI. Both NSPT and OHI demonstrated improvements in other clinical parameters as well as HbA1c and CRP levels.